Interactions between environment, wild animals and human leptospirosis - Ullmann, L. S. [UNESP] (2011)
Leptospirosis, a worldwide distributed zoononis caused by bacteria of the genus Leptospira (antigenically classified into serovars), may be direct or indirectly transmitted through infected urine or environment. Several domestic and wild animals are leptospirosis reservoirs. The disease presents occupational character since it is widely reported in professionals that work in humid environments - such as sewage workers and fishermen - and in places where rodents or susceptible animals are found, like slaughterhouses and veterinary clinics. In developing countries, outbreaks are related to lack of sanitation, overcrowding in inadequate housing and climatic conditions. In developed countries, sporadic cases occur in aquatic recreational activities including swimming and triathlon. The diagnosis of leptospirosis is complex due to the variety of symptoms, disease severity and the lack of techniques that are able to early detect the infection. Thus, leptospirosis causes numerous public health problems and educational activities are very important to its control.